(untitled) (Research, Society and Development, 2022)
Objective: to evaluate cardiovascular risk and the level of activation in individuals undergoing hemodialysis treatment. Materials and methods: this is a quantitative research, with an analytic approach, developed with 145 individuals with chronic kidney disease in stage terminal and undergoing hemodialysis treatment on outpatient. Data were collected through the application of a sociodemographic and clinical questionnaire data, and the Framingham score and PAM-13 subjective construct were applied. Results: most research participants were male (52.41%); self-reported that they were not black (99.12%); were residents of Uberlândia (84.14%) and lived without a partner (53.79%). The main causes of chronic kidney disease identified were diabetic nephropathy and hypertensive nephrosclerosis. Regarding cardiovascular risk stratification, 46.21% of patients had a low risk (< 10%) for the occurrence of cardiovascular events in the next 10 years. In the assessment of the level of activation by the PAM-13, the very low level prevailed among the patients (43.45%). Conclusion: Individuals with chronic kidney disease on outpatient hemodialysis had a low risk for the occurrence of cardiovascular disease in 10 years according to the Framingham Score and a low level of activation for managing self-care using the PAM-13 construct, and there was no dependency between the instruments used.